Relationship between work facilities and work discipline on employee performance - Malalia, Irna; Oktaviani, Via; Damayanti, Fina; Haryadi, Didit; Wahyudi, Wahyudi (International Journal of Applied Finance and Business Studies, 2024)
Effective management, thinking about the importance of human resources. Employee performance is an important factor influencing success. In an organization, this is one of the most important functions of a company. The purpose of this study is threefold: to examine the effect of work facilities on employee performance, determine the effect of work discipline on employee performance, and determine the effect of the combined effect of work facilities and work discipline on employee performance. This study used a quantitative methodology with data collection through questionnaires. This research was conducted at PT Mitsuba Indonesia Serang Branch with a population of 41 respondents. The sample of this study was determined using saturated sampling techniques. The data obtained from the questionnaire were analyzed using the IBM SPSS Version 26 software program. Research findings show no significant effect of work facilities on employee performance. These findings indicate that there are pleasant and satisfactory working conditions in employees. forherence to work discipline has been shown to have an important and beneficial impact on overall employee performance. This finding shows a positive correlation between work facilities, employee discipline, and performance. This research is expected to make theoretical contributions to the literature in the context of human resource management